PENINGKATAN KEMAMPUAN BERHITUNG MELALUI PERMAINAN ULAR TANGGA PADA ANAK USIA DINI - Mujtahidin, Samsul; Hardianti, Farlian; Rachman, Sry Anita (Berajah Journal, 2024)
Early Childhood Education is an educational institution that develops six aspects of development, one of which is cognitive development. Stimulation of cognitive development in early childhood includes recognizing the concept of numbers, counting and stating the concept of numbers. However, the conditions currently occurring in the field are the demands of parents who want to see their children be able to read, writing and arithmetic because they are worried that their children will not be accepted into favorite elementary schools which require passing the reading, writing, and arithmetic test for prospective students. This research is classroom action research, which was conducted in 2 cycles. The subjects in this study were the children of Group B TK Al-Khairiyah with a total of 20 children. Data collection techniques in this study are observation and documentation. Data analysis techniques using quantitative descriptive. The results of the study showed that the ability of children at the pre-cycle stage is still in the developing stage. In cycle I, the average score was 2.8 with a percentage of 62.52% in the 'Developing as Expected' category. And in cycle II there was a pretty good increase, with a percentage reaching 80%. Therefore, it can be said that the snakes and ladders game can improve the numeracy skills of young children.